Development of body composition, hormone profile, physical fitness, general perceptual motor skills, soccer skills and on-the-ball performance in soccer specific laboratory test among adolescent soccer players - Vänttinen, T.; Blomqvist, M.; Häkkinen, K. (Journal of Sports Science & Medicine, 2010)
The aim of the present study was to examine the development of on-the-ball skills in soccer-specific laboratory test and to examine how traditional measures of body composition, hormone profile, physical fitness, general perceptual motor skills and soccer skills were related to performance measured in open skill environment among 10, 12, and 14-year-old regional male soccer players (n = 12/group). The measured variables were height, weight, fat, muscle mass, testosterone, 10m sprint, agility, counter movement jump, peripheral awareness, Eye- Hand-Foot coordination, passing skill, dribbling skill and on-the-ball skills (performance time and passing accuracy) in soccer-specific laboratory test. A significant main effect by age was found in all measured variables except in fat, in peripheral awareness and in passing accuracy. In discriminant analysis 63.9% (? = 0.603, F = 4.600, p < 0.01) of the players were classified correctly based on physical fitness and general perceptual motor skills into three ability groups originally classified with performance time in soccer-specific laboratory test. Correlation co- efficient analysis with-in age groups revealed that variables associated with performance time in soccer-specific laboratory test were peripheral awareness (r = 0.72, p < 0.01) in 10-year-olds; testosterone (r = -0.70, p < 0.05), dribbling skill (r = 0.73, p < 0.01) and passing skill (r = 0.73, p < 0.01) in 12-year-olds; agility (r = 0.79, p < 0.01), counter movement jump (r = - 0.62, p < 0.01), dribbling skill (r = 0.80, p < 0.01) and passing skill (r = 0.58, p < 0. 05) in 14-year olds. Corresponding relationships with passing accuracy were weight (r = 0.59, p < 0.05), fat (r = 0.66, p < 0.05), 10m sprint (r = 0.71, p < 0.01) and countermovement jump (r = -0.64, p < 0.05) in 10-year-olds; Eye-Hand-Foot coordination (r = 0.63, p < 0.05) in 14-year- olds. The relationship between soccer-specific anticipation time and performance time in soccer- specific laboratory test was significant only in the 14-year-old age group (r = 0.76, p < 0.01). To conclude, on-the-ball skill performance in soccer-specific laboratory test improved with age and it seemed that soccer-specific perceptual skills became more and general perceptual motor skills less important with age in soccer-specific laboratory test.